2000
DOI: 10.1097/00007890-200012150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Portal Fibrosis in Pediatric Liver Transplant Recipients

Abstract: The incidence of PF within 1 year post liver transplantation was 31%. This finding was accompanied by cholestatic liver function test abnormalities. Factors predisposing to PF were a prolonged cold ischemia time, biliary complications, and a positive cytomegalovirus recipient status. Acute rejection seemed to prevent for PF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
7

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 35 publications
5
53
7
Order By: Relevance
“…The prevalence of fibrosis at 1 year in the current study (23%) is similar to that reported by Peeters et al, 19 who observed portal fibrosis in 31% of transplanted children within 1 year post-transplantation, mainly related to graft ischemia and biliary complications. In the current study, children with biliary obstruction also exhibited a high rate of fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of fibrosis at 1 year in the current study (23%) is similar to that reported by Peeters et al, 19 who observed portal fibrosis in 31% of transplanted children within 1 year post-transplantation, mainly related to graft ischemia and biliary complications. In the current study, children with biliary obstruction also exhibited a high rate of fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…27 In addition, the occurrence of biliary complications is an independent risk factor for portal fibrosis 1 year after transplantation. 38 These findings emphasize the importance of preventing biliary complications by securing vascularization of the bile ducts and checking the transection surface of technical-variant grafts for bile leakage.…”
Section: Discussionmentioning
confidence: 86%
“…Interstitial ET-1 was associated with a lower cellular rejection score, suggesting a dissociation between rejection and fibrosis, as has been shown in pediatric liver transplants. 14 The concept of fibrosis after transplantation has been thoroughly examined by Armstrong and his colleagues, 15 who evaluated serial endomyocardial biopsies on 50 cardiac transplant patients followed over 5 years. The investigators showed that myocardial fibrosis develops early and remains modestly elevated 2 months after transplant, indicating that peri-transplant factors might be responsible for this fibrotic process.…”
Section: Discussionmentioning
confidence: 99%